HUBUNGAN KEPERCAYAAN DIRI DENGAN PERILAKU KONSUMTIF MENGGUNAKAN PRODUK PEMUTIH WAJAH - Lathifatul Ulfa Agus (Jurnal Riset Psikologi, 2018)
Abstract: Relationship between self confidence andconsumtive behavior using whitening products.This study aims to see the relationship of self-confidence with consumptive behavior using facial whitening products. The design of this study was correlation quantitative. Population in this study was the student of cosmetology department, Padang State University.Total sample was 70 student by using random sampling technique. This study uses confidence and consumer behavior scale. Data analysis was using Karl Pearson product moment correlation. The results showed that there was a significant negative relationship between self-confidence and consumptive behavior in Cosmetology Students of Padang State University using facial whitening products with correlation coefficient values of -0.261 and p = 0.029 (p <0.05).Keywords: Self confidence, consumtive behavior, face whitening products.Abstrak: Hubungan kepercayaan diri dengan perilaku konsumtif menggunakan produk pemutih wajah. Penelitian ini bertujuanuntukmelihathubungankepercayaan diri dengan perilaku konsumtif menggunakan produk pemutih wajah.Desainpenelitian yangdigunakanadalahkuantitatifkorelasional.Populasipadapenelitianiniadalah Mahasiswi Tata Rias Universitas Negeri Padang.Teknik pengumpulan sampelrandom sampling dengan jumlah sampel 70 orang.Penelitianinimenggunakanskala kepercayaan diri, dan skala perilaku konsumtif. Teknik analisis data yang digunakanyaitukorelasi product momentdari Karl Pearson. Hasil penelitian menunjukan terdapat hubungan negatif yangsignifikan antara kepercayaan diri dengan perilaku konsumtif pada Mahasiswi Tata Rias Universitas Negeri Padang yang menggunakan produk pemutih wajah dengan nilai koefisien korelasi sebesar -0,261 dan p= 0,029 (p<0,05).Kata kunci: Kepercayaan diri, perilaku konsumtif, produk pemutih wajah.